Prospects of Anticorruption Legal Regulation in the Law of the European Union: International and National Aspects - G. V. Petrova (Московский журнал международного права, 2010)
The article is devoted modern actual theoretical and practical problems of interaction international anticorruption and financial rules of law in sphere of prevention of financing of terrorism, corruption and washing up of illegal incomes in EU. It is shown that operating mechanisms of the currency control and bank supervision of EU of financial operations of subjects are necessary for strengthening anticorruption measures. International legal norms against financial criminality, corruption and terrorism financing should be transformed to norms of the national administrative, financial, anticorruption law. Theoretical positions of scientists in the field of the European Law about use of the integration law in the mechanism of struggle against financial criminality, legalization of criminal incomes and corruption are consecrated.